Medicinal plant knowledge of the Bench ethnic group of Ethiopia: an ethnobotanical investigation - Woldu Zerihun; Asfaw Zemede; Giday Mirutse; Teklehaymanot Tilahun (BMC, 2009)
Abstract Background Plants have traditionally been used as a source of medicine in Ethiopia since early times for the control of various ailments afflicting humans and their domestic animals. However, little work has been made in the past to properly document and promote the knowledge. Today medicinal plants and the associated knowledge in the country are threatened due to deforestation, environmental degradation and acculturation. Urgent ethnobotanical studies and subsequent conservation measures are, therefore, required to salvage these resources from further loss. The purpose of the present study was to record and analyse traditional medicinal plant knowledge of the Bench ethnic group in Southwest Ethiopia. Methods Semi-structured interviews were conducted with Bench informants selected during transect walks made to houses as well as those identified as knowledgeable by local administrators and elders to gather data regarding local names of medicinal plants used, parts harvested, ailments treated, remedy preparation methods, administration routes, dosage and side effects. The same method was also employed to gather information on marketability, habitat and abundance of the reported medicinal plants. Purposive sampling method was used in the selection of study sites within the study district. Fidelity Level (FL) value was calculated for each claimed medicinal plant to estimate its healing potential. Results The study revealed 35 Bench medicinal plants: 32 used against human ailments and three to treat both human and livestock ailments. The majority of Bench medicinal plants were herbs and leaf was the most frequently used part in the preparation of remedies. Significantly higher average number of medicinal plants was claimed by men, older people and illiterate ones as compared to women, younger people and literate ones, respectively. The majority of the medicinal plants used in the study area were uncultivated ones. Conclusion The study revealed acculturation as the major threat to the continuation of the traditional medical practice in the study area. Awareness should, therefore, be created among the Bench community, especially the young ones, by concerned organizations and individuals regarding the usefulness of the practice.